Records management practices of international organizations in the Philippines a survey - Nofuente, Evelyn D.; Hidalgo, Namnama P.; Ramirez, Josefina J. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1981)
This study is a descriptive survey of thirteen (13) international organizations based in the Philippines. It aims to survey established standards, procedures and techniques of records keeping practices of international organizations. It also aims to describe the processes by which these organizations plan the creation of records, determine the utilization of a records classification scheme, the reference activities of all records, the filing systems being used and to find out how many of these organizations have already established a records retention and disposition schedule, a vital records protection program and the existing procedures governing the preservation of records, its orderly retirement and the system being utilized to eliminate unnecessary duplication of documents. The normative survey method of research was employed using the questionnaire and interview techniques. Records administrators from thirteen (13) international organizations served as respondents.
The major findings gleaned from the survey results are quite revealing. The organizational units charged with the records management functions are found to be subordinated to larger units of the organization whose primary functions are of a "housekeeping" nature. Records staff are relatively small in number and oftentimes untrained to do records work. Responses reveal that majority of the organizations usually receive copies of all incoming and outgoing correspondences, memoranda and other records-related materials for file. There are records that are being distributed internally, externally or both. The centralized filing system is the most commonly used and findings reveal that records administrators are mainly concerned with the filing practices than with any other phase of records management program. A workable file classification scheme is in use and the most commonly used scheme is the subject-numeric type where a code number is assigned for a particular subject field. The scheme was patterned after the Dewey Decimal Classification System. A charge-out system is devised for borrowed files. The idea of a Records Center is not yet very popular so that inactive records are still under the control of individual departments. No sophisticated archives program exists in many organizations. Hence, materials of permanent and historical value are just preserved in records center boxes. Only two organizations surveyed have a separate program for their vital records protection by microfilming valuable records. Only seven organizations have already established retention and disposition schedules and valueless records are being disposed of by shredding, burning, selling, or by tearing the documents. The application and up-dating of the disposal and retention schedules are done on a very irregular basis.
In conclusion, it has been found that the records management practices of international organizations seem to vary depending on their own particular needs. The records management program is oftentimes taken for granted by the top management people and staff are usually not trained to do records work. Something is still left to be done to improve the records management programs of international organizations. These include improvement of such aspects as the records creation phase, records distribution, organization of files, records center operation, vital records protection, records disposition and the records retention aspect.
Recommendations are offered to achieve a sound records management program. There should be a centralized control and management of all company records. Staff should be asked to attend records management seminars to make them fully aware of the latest procedures and practices in records management. Guidelines should be issued governing policies on records creation so as to prevent excessive duplication of records being created and on records distribution so as to avoid unnecessary reprinting of documents and thus attain office economy. The classification scheme should be revised regularly. Inactive records should be segregated from active files and a records center should now be established. Vital records protection program should be given due attention and the records disposition and retention schedules should be regularly reviewed so that unnecessary records can be immediately disposed of when no longer needed for office operations.
Typescript
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: International organization; Records -- Management